“What stood in the Post Office / With Pearse and Connolly?”: Heroism, Timeliness, and Timelessness in Some of Yeats’s Plays - Bődy, Edit (Hungarian Journal of English and American Studies, 2020)
The essay discusses a frequently recurring type of hero found in William Butler Yeats’s plays, including the last one, The Death of Cuchulain (1939). This hero-figure occurs quite early in Yeats’s oeuvre: The Green Helmet (1910), for example, already focuses on the definition of hero and heroism and different versions of this hero type also occur in other plays, such as The King’s Threshold (1904) and The Player Queen (1922). In dramas, where this motif plays an important role, his source is in part Nietzsche’s tragic hero completed with other features. As early as The Green Helmet, Yeats defines what makes a hero: apart from bravery, also gaiety, a kind of ecstasy is needed. Cuchulain’s goal to become the hero, smiling even in the shadow of death, is achieved in Yeats’s last play, and the Cuchulain-image emerging from the Anima Mundi binds past and present. (EB)